Influence of operational parameters on the start-up of a flocculation airlift bioreactor - Sousa, M. Luísa (1994)
The evolution of the fermentation parameters of a flocculating Saccharomyces yeast strain started up in a continuously operated internal loop airlift bioreactor was compared at different aeration rates (0.02 and 0.1 v.v.m., where v.v.m. represents the volume of air per volume of fermenter per minute and has the units 11−1 min−1) and dilution rates (0.1 and 0.2 h−1). The floc size distributions obtained were found to be different. The operating parameters do not seem to affect the glucose consumption rates, but instead affect the stoichiometry of its conversion to either ethanol or biomass, suggesting a shift in the metabolic mechanisms as biomass builds up. Oxygen availability was not uniform in the fermenter, according to the global volumetric mass transfer coefficients determined. The subsequent results establish a strong influence of the dilution and aeration rates on the measured variables (glucose, ethanol and biomass concentrations) and the calculated kinetic parameters (specific rates of glucose consumption, ethanol production and biomass growth).